2019
DOI: 10.35410/ijaeb.2019.4418
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Morphological and Chemical Variability in Different Fennel (Foeniculum Vulgare Mill.) Cultivars

Abstract: Knowledge on phenotypic and chemical diversity among fennel (Foeniculum vulgare Mill.) cultivars is a milestone in the improvement of this specie which is considered as one of the most important medicinal plants. For this purpose, the present study was conducted in order to compare for the first time fennel cultivars regarding their agro-morphological traits as well as their essential oil yield and composition. Ten fennel cutivars were cultivated in a randomized completely block design whereas the seeds essent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
(22 reference statements)
2
1
1
Order By: Relevance
“…This characteristic affect both EOY% and TAY% of the evaluated fennel population of the present study. These results are consistent with the results of Sefidan et al [44] and Kalleli et al [45]. TAY% (as a second dependent variable) had the strongest positive correlation with HI (R = 0.823) followed by SY/P (R = 0.693), SY/m 2 (R = 0.693), EOY% (R = 0.590), NS/P (R = 0.573), NU (R = 0.572) and LFI (R = 0.456), as well as a negative significant correlation with LLOI (Figure 2).…”
Section: Selection Of Input Variablessupporting
confidence: 94%
See 1 more Smart Citation
“…This characteristic affect both EOY% and TAY% of the evaluated fennel population of the present study. These results are consistent with the results of Sefidan et al [44] and Kalleli et al [45]. TAY% (as a second dependent variable) had the strongest positive correlation with HI (R = 0.823) followed by SY/P (R = 0.693), SY/m 2 (R = 0.693), EOY% (R = 0.590), NS/P (R = 0.573), NU (R = 0.572) and LFI (R = 0.456), as well as a negative significant correlation with LLOI (Figure 2).…”
Section: Selection Of Input Variablessupporting
confidence: 94%
“…This characteristic affect both EOY% and TAY% of the evaluated fennel population of the present study. These results are consistent with the results of Sefidan et al [44] and Kalleli et al [45]. Although HI and LFI were significantly correlated with EOY% and TAY%, according to the SWR analysis, these parameters could not be recognized as appropriate input variables (Tables 3 and 4).…”
Section: Selection Of Input Variablessupporting
confidence: 91%
“…Yadav et al [ 69 ] and Kumar et al [ 4 ] reported that seed yield had significant and positive correlations with umbels per plant, the number of umbelets per umbel, and the number of seeds per umbelets in fennel. Contrary to our results regarding the relationships between the yield and its components, Kalleli et al [ 70 ] reported a negative significant correlation between seed yield and 1000-seeds weight in fennel. On the other hand, in both populations STI and YSI showed significant and positive correlations with SYP and its components under normal and water deficit conditions.…”
Section: Discussioncontrasting
confidence: 99%
“…Based on the top PC scores in principal component 1 and principal component 2, two genotypes HAJ-07 and AA-02 are selected. These results are in relevance with the results quoted by Kalleli et al, (2019) [6] , YALDIZ et al, (2020) [10] and Modareskia et al, (2022) [8] .…”
Section: Resultssupporting
confidence: 92%